Culturally Responsive Music Education: Integrating the Minangkabau Song 'Batu Tagak' in Primary School Learning - Delvia Mona; Suharto; Syahrul Syah Sinaga; Ardipal; Wadiyo (Paedagogi: Jurnal Kajian Ilmu Pendidikan (e-journal), 2026)
This study aims to analyze the implementation of the Minangkabau song "Batu Tagak" in elementary school music education from a Culturally Responsive Music Education perspective. This research uses a qualitative approach with a case study design. Data were collected through observation, interviews, documentation, and analysis of the song's sheet music, then analyzed using thematic analysis techniques. The results show that the musical characteristics of 'Batu Tagak,' which are simple and easy to learn, support its use as an effective learning resource. Exploring the lyrics helps students understand Minangkabau cultural values related to family relationships, the tradition of merantau (migration), attachment to hometown, and cultural symbols represented in the song. Through singing activities, discussions, and reflections, students actively construct cultural meaning by connecting the song's content with their own experiences. This learning also increases student engagement and strengthens their cultural identity as part of the Minangkabau community. The findings indicate that the musical characteristics of the song and students' cultural experiences work together as a pedagogical mechanism that supports Culturally Responsive Music Education practices. This study concludes that 'Batu Tagak' functions not only as a musical learning material but also as a pedagogical medium that links students' social and cultural experiences with the learning process in elementary schools. These findings demonstrate that traditional songs have the potential as a learning resource in Culturally Responsive Music Education practices, as well as a means of preserving local culture through education